Factors that inhibit science teachers' implementation of learner autonomy after a professional development collaboration - Sathasivam, Renuka V.; Abd Rauf, Rose Amnah; Krishnan, Dhesegaan Bala; Rasul, Mohamad Sattar; Leong, Kwan Eu (Primrose Hall Publishing Group, 2019)
Developing learner autonomy can improve learners' outcomes. Teaching students autonomy is a cultural endeavour. Therefore teachers operating from an Asian heritage may struggle to implement learner autonomy. Teachers face several pressures when implementing learner autonomy, and require development. This paper investigates what prevented science teachers from implementing autonomy-supportive strategies after a Collaborative Professional Development Programme (CPDP). CPDP guides science teachers to implement learner autonomy, with Assessment for Learning (AfL) principles. It flexibly and expertly encourages teachers to strategise their autonomy. This study is part of a more extensive study. Three primary science teachers participated in the CPDP. They were interviewed afterwards to elicit inhibiting factors, which included lack of time to prepare students for examinations and resources (pressure from above); non-cooperative students (pressure from below) and teachers' beliefs that students were unable to become autonomous (pressure from within). Detailed recommendations are given, with implications for professional programme developers and policymakers.. © 2019 Primrose Hall Publishing Group.